Pengaruh Pendidikan Kesehatan Terhadap Tingkat Pengetahuan Remaja Putri Tentang Anemia Di Smp Negeri 10 Kota Bengkulu - Puput Adilla Putri Alam; Yesi Putri; Emi Pebriani (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Anemia is one of the health problems that often occurs in adolescent girls and can have an impact on health, concentration in learning, and academic achievement. One of the efforts that can be made to prevent anemia is through health education. This study aims to determine the effect of health education on the level of knowledge of adolescent girls about anemia at SMP Negeri 10, Bengkulu city. This study used a pre-test and post-test design with a quantitative approach. The study was conducted on January 21-22, 2026, with 52 seventh-grade female students as respondents. The instrument used was a questionnaire on knowledge about anemia. Health education was provided using PowerPoint media accompanied by the provision of Fe Tablets (TTD). Data analysis was performed using univariate and bivariate methods. The normality test used Shapiro-Wilk and the statistical test used was the Wilcoxon Signed Rank Test. The results showed that before being given health education, most respondents had sufficient knowledge (44.2%) and there were still respondents with insufficient knowledge (38.5%). After receiving health education, there was an increase in the level of knowledge, with most respondents in the sufficient knowledge category (53.8%) and almost half of the respondents in the good knowledge category (46.2%). The Wilcoxon test results showed a p-value of 0.000 (p < 0.05), which means that health education had an effect on the level of knowledge of adolescent girls about anemia. It can be concluded that health education has an effect on increasing the level of knowledge of adolescent girls about anemia. Therefore, health education needs to be continued as an effort to prevent anemia from an early age in adolescent girls.